Amino acetaldehyde conformers: structure and spectroscopic properties. Issue 2 (19th December 2019) - Redondo, Pilar; Sanz-Novo, Miguel; Largo, Antonio; Barrientos, Carmen
ABSTRACT: We present a computational study of the different conformers of amino acetaldehyde. This molecule is a precursor of glycine and also an isomer of the detected molecules acetaldehyde and methylformamide. In addition, a previous theoretical result shows that amino acetaldehyde could be formed from the gas phase reaction of formamide with CH$_{5}^{+}$ . Different computational approaches, going from density functional theory (DFT) to coupled cluster (CC) calculations, are employed for the characterization of the amino acetaldehyde conformers. We locate four low-lying conformation on the singlet potential energy surface (PES), two with a synperiplanar arrangement of the carboxylic oxygen atom and the NH2 group, and the other two conformers with an anticlinal disposition. All levels of theory predict the conformer with a synperiplanar arrangement and the H atoms of the NH2 group pointing in the direction of the oxygen, denoted as in - sp -amino acetaldehyde, as the most stable. The viability of the interconversion processes between the four conformers in space is analysed. Relevant spectroscopic parameters to rotational spectroscopy with 'spectroscopic' accuracy at the composite level are reported. Vibrational frequencies and infrared intensities are also computed at the CC with single and double excitations (CCSD) level including anharmonic corrections. This information could help in the experimental characterization of amino acetaldehyde that could be considered as a good candidate molecule to be searched for in space.